2017
DOI: 10.1038/nrneph.2017.157
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic and endocrine functions of adipose tissue: implications for kidney disease

Abstract: Excess adiposity can induce adverse sequelae in multiple cell types and organ systems. The transition from the lean to the obese state is characterized by fundamental cellular changes at the level of the adipocyte. These changes affect the local microenvironment within the respective adipose tissue but can also affect nonadipose systems. Adipocytes within fat pads respond to chronic nutrient excess through hyperplasia or hypertrophy, which can differentially affect interorgan crosstalk between various adipose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(119 citation statements)
references
References 217 publications
3
92
0
8
Order By: Relevance
“…We speculated that AT1R-induced PKCα-NOX activation involved in obesity-induced renal oxidative stress and apoptosis in this study. The increase in renal oxidative stress, inflammation and apoptosis has been shown to be a factor inducing podocyte injury in obesity (Zhu & Scherer 2017). In this study, we found the increase level of NOX4 and subunit of NOX2 in the kidney concomitant with the increased MDA level and 4-HNE expression.…”
Section: Figuresupporting
confidence: 61%
“…We speculated that AT1R-induced PKCα-NOX activation involved in obesity-induced renal oxidative stress and apoptosis in this study. The increase in renal oxidative stress, inflammation and apoptosis has been shown to be a factor inducing podocyte injury in obesity (Zhu & Scherer 2017). In this study, we found the increase level of NOX4 and subunit of NOX2 in the kidney concomitant with the increased MDA level and 4-HNE expression.…”
Section: Figuresupporting
confidence: 61%
“…Oxidative stress may contribute to the development of ER stress by promoting protein unfolding and activating the unfolded protein response. In fact, it has been shown that dietary saturated FFAs induce ER stress in kidneys of animal models [21] and in renal culture cells [25]. Moreover, insulin resistance affects the kidney, especially the podocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Obwohl bereits mit Beobachtungen, dass Geschlechtshormone [6][7][8][9][10] und Adipsin/complement factor D [18] aus dem Fettgewebe sezerniert werden, die endokrine Funktion dieses Gewebes nahegelegt wurde, wird die Entdeckung von Leptin [11] und wenig später von Adiponektin [13] als Beginn der Adipokinforschung angesehen [12]. Die systematische Suche nach Signalen, die aus dem Fettgewebe kommen, hat in den letzten Jahren dazu geführt, dass über 600 Adipokine beschrieben wurden [6,19], die wesentliche biologische Prozesse regulieren (▶Abb.…”
Section: Adipokine Regulieren Biologische Prozesseunclassified
“…Adipositas führt zu einer Fehlfunktion des Fettgewebes, die durch ektope Fettverteilung (z. B. viszeraler Fettakkumulation, Leberverfettung), Hypertrophie von Adipozyten, Veränderungen der zellulären Zusammensetzung und der intrazellulären Matrix, aber auch eine Änderung der aus dem Fettgewebe sezernierten Moleküle gekennzeichnet ist [6][7][8][9][10]. Erst mit der Entdeckung von Leptin vor über 20 Jahren wurde die Bedeutung der endokrinen Funktion des Fettgewebes erkannt [11].…”
Section: Introductionunclassified
See 1 more Smart Citation